Aset Kripto dan Partisipasi Generasi Muda dalam Investasi: Tinjauan Hukum Investasi serta Implikasinya bagi Kebijakan Daerah Kota Surakarta - Muhammad Winarto; Tegar Wibowo; Arseto Endro Supriyanto (Badan Riset dan Inovasi Daerah Kota Surakarta, 2026)
The development of crypto assets has become a global investment trend, particularly among the younger generation in Indonesia, who are highly adaptable to digital technology. However, in cities like Surakarta, the rapid adoption of crypto assets presents a challenge, as the pace of youth investment surpasses the adaptation of local legal protection systems. This study examines the participation of young investors in crypto assets from a legal perspective and analyzes the implications for regional policies in Surakarta. Using a qualitative approach with systematic library research, data were gathered from indexed journals and regulations, and analyzed through a juridical qualitative approach and content analysis. The findings reveal that young investors in Surakarta are vulnerable to scams and have limited legal knowledge, despite their high digital literacy. The dualistic national legal framework, which regulates crypto as a commodity, fails to address the protection gap. This highlights the need for proactive local policy intervention. Rather than introducing new regulations, the study suggests an educative, non-regulatory approach, such as establishing a Collaborative Digital Investment Education Program, creating a Regional Crypto Consultation Task Force, and offering Blockchain-Based Innovation Incentives. These initiatives aim to guide youth participation in crypto investment safely and sustainably, while strengthening the local economy and MSMEs.